Tanggung Jawab Hukum Platfrom Digital Terhadap Perlindungan Keselamatan Dan Kesehatan Kerja Bagi Pekerja GIG Economy Di Indonesia - Anindya Paramesti Kusumo; Merline Eva Lyanthi (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
The development of the digital economy has encouraged the emergence of platform-based work models known as the gig economy, in which workers obtain jobs through digital applications with characteristics of flexible working arrangements and on-demand employment systems. Although this model provides greater opportunities for income generation, it also raises legal issues, particularly regarding occupational safety and health (OSH) protection for gig economy workers, such as online transportation drivers and digital delivery couriers. Work systems controlled through algorithms, incentive mechanisms, rating systems, and performance targets may influence workers’ behavior and increase the risk of fatigue, physical and mental health problems, and occupational accidents. This study aims to analyze the legal responsibility of digital platforms in providing occupational safety and health protection for gig economy workers in Indonesia and to formulate an ideal legal accountability framework to ensure the protection of platform workers’ rights. This research employs a normative legal research method using statutory, conceptual, and analytical approaches. The findings indicate that although the legal relationship between digital platforms and gig economy workers is formally classified as a partnership relationship, platforms maintain significant control over work arrangements through algorithm management, task allocation, performance evaluation, and incentive structures. Such control demonstrates that platforms bear certain legal responsibilities in ensuring the occupational safety and health protection of workers. An ideal legal responsibility framework should include the recognition of a specific legal status for platform workers, the implementation of occupational safety and health principles within digital work systems, the provision of employment social security protection, risk prevention mechanisms, accident compensation schemes, and stronger government regulation and supervision over platform-based work arrangements in Indonesia.